2016
DOI: 10.1371/journal.pbio.1002387
|View full text |Cite
|
Sign up to set email alerts
|

Tel1 and Rif2 Regulate MRX Functions in End-Tethering and Repair of DNA Double-Strand Breaks

Abstract: The cellular response to DNA double-strand breaks (DSBs) is initiated by the MRX/MRN complex (Mre11-Rad50-Xrs2 in yeast; Mre11-Rad50-Nbs1 in mammals), which recruits the checkpoint kinase Tel1/ATM to DSBs. In Saccharomyces cerevisiae, the role of Tel1 at DSBs remains enigmatic, as tel1Δ cells do not show obvious hypersensitivity to DSB-inducing agents. By performing a synthetic phenotype screen, we isolated a rad50-V1269M allele that sensitizes tel1Δ cells to genotoxic agents. The MRV1269MX complex associates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
116
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 52 publications
(134 citation statements)
references
References 74 publications
18
116
0
Order By: Relevance
“…We further extended the previous observation that tel1D cells are hypersensitive to CPT [5,6] by showing that Tel1 kinase activity is specifically required for CPT resistance. In fact, either the lack of Tel1 or the expression of a tel1-kd allele, which causes G2611D, D2612A, N2616K and D2631E amino acid substitutions that abolish Tel1 kinase activity in vitro [22], decreased cell viability in the presence of CPT, but not in the presence of the alkylating agent methyl methanesulfonate (MMS), the DNA replication inhibitor hydroxyurea (HU) or the radiomimetic drug phleomycin ( Fig 1A and B).…”
Section: Tel1 Specifically Supports Resistance To Camptothecinsupporting
confidence: 80%
“…We further extended the previous observation that tel1D cells are hypersensitive to CPT [5,6] by showing that Tel1 kinase activity is specifically required for CPT resistance. In fact, either the lack of Tel1 or the expression of a tel1-kd allele, which causes G2611D, D2612A, N2616K and D2631E amino acid substitutions that abolish Tel1 kinase activity in vitro [22], decreased cell viability in the presence of CPT, but not in the presence of the alkylating agent methyl methanesulfonate (MMS), the DNA replication inhibitor hydroxyurea (HU) or the radiomimetic drug phleomycin ( Fig 1A and B).…”
Section: Tel1 Specifically Supports Resistance To Camptothecinsupporting
confidence: 80%
“…This change upon binding DNA decreases the ability of the zinc hook to make intra-molecular interactions and promotes intermolecular interactions between two MRN complexes bound to separate DNA strands. Indeed, intermolecular MRN DNA end tethering has been observed via AFM, and subsequent studies have also observed MRX/MR-stimulated DNA end bridging in vitro and in vivo (Cassani et al, 2016; Chen et al, 2001; Deshpande et al, 2014; Kaye et al, 2004; Lobachev et al, 2004; Moreno-Herrero et al, 2005). However, another in vivo study that monitored fluorescent reporters proximal to broken DNA ends in human cells has questioned the importance of these DSB-bridging activities at restriction endonuclease-created DNA breaks (Soutoglou and Misteli, 2008).…”
Section: Dna End Recognition and Early Processingmentioning
confidence: 88%
“…Tel1 promotes MRX recruitment, whereas Rif2 acts as a negative regulator by enhancing ATP hydrolysis that opens Rad50, facilitating MRX release from DNA (184). In line with insights from yeast experiments, changes in expression and posttranslational modification of MRN and telomeric proteins are associated with various diseases in humans (185187).…”
Section: Mrn and Dysfunctional Telomeresmentioning
confidence: 99%